ASEAN'S ATTEMPTS IN SECURITIZING WOMEN'S RIGHTS AT THE REGIONAL AND STATE LEVEL (MYANMAR) - Yayusman, Meilinda Sari; Mantovani, Anisa Pratita Kirana (Research Center for Regional Resources-Indonesian Institute of Sciences (P2SDR-LIPI), 2019)
AbstractThis paper aims to examine the extent to which ASEAN has attempted to securitize womens rights at the regional and state level. Securitization theory formulated by the Copenhagen School expounds a set of securitization process by which a certain issue can be categorized as a security issue that should be concerned. In securitization process, an issue should follow three stages: a) non-politicized; b) politicized; c) securitized. Speech act and the acceptance of audience are also paramount in the process. Throughout these steps, the extent to which ASEAN has put endeavor to securitize womens rights can be determined. At the regional level, attempts through declarations and commitments among member states can be analyzed to indicate ASEANs concrete endeavor to take into account womens rights as an issue that should be securitized. In the meantime, at the state level, Myanmar, a newly democratic country in Southeast Asia, will be analyzed. Womens rights in Myanmar are of grave concern and as a consequence, securitizing women issues especially the rights of women is of great importance. The limited role of ASEAN has nonetheless given consequences to the action given to a state. Myanmar has become a concrete example to show that ASEAN merely contributes an influence or encouragement to its member states to promote womens rights. Securitizing womens rights at the state level is arguably difficult due to the principle of non-interference that ASEAN has. Keywords: securitization theory, ASEAN, Myanmar, womens rightsAbstrakTulisan ini bertujuan untuk melihat sejauh mana ASEAN telah berusaha melakukan sekuritisasi terhadap hak-hak wanita di tingkat regional dan negara. Teori sekuritisasi yang dirumuskan oleh Copenhagen School menjelaskan secara terperinci tentang proses sekuritisasi di mana sebuah isu tertentu dapat dikategorikan sebagai isu keamanan yang perlu diperhatikan. Dalam proses sekuritisasi, sebuah isu perlu melalui tiga tahapan, yakni a) tidak dipolitisasi; b) dipolitisasi; c) sekuritisasi. Pidato dan penerimaan dari para pendengar isu juga merupakan hal penting dalam proses sekuritisasi. Melalui langkah-langkah ini, sejauh mana ASEAN telah berusaha untuk melakukan sekuritisasi terhadap isu hak-hak wanita dapat ditentukan. Di tingkat regional, upaya-upaya melalui deklarasi dan komitmen antarnegara anggota dapat dianalisis untuk melihat usaha nyata ASEAN dalam memperjuangkan hak-hak wanita sebagai isu yang perlu disekuritisasi. Di samping itu, di tingkat negara, Myanmar sebagai negara demokrasi baru di Asia Tenggara, akan dianalisis. Hak-hak wanita di Myanmar mendapat perhatian utama, sehingga sekuritisasi terhadap isu-isu hak-hak wanita merupakan hal yang penting. Namun, peran terbatas ASEAN memberikan konsekuensi dalam upaya sekuritisasi di tingkat negara. Myanmar merupakan contoh nyata untuk memperlihatkan bahwa upaya ASEAN dalam sekuritisasi hak-hak wanita hanya sebatas memberikan pengaruh atau dukungan. Melakukan sekuritisasi terhadap hak-hak wanita di tingkat negara dapat dikatakan sulit karena prinsip non-intervensi yang dimiliki ASEAN.Kata kunci: teori sekuritisasi, ASEAN, Myanmar, hak-hak wanita